Re-Kreasi Atap: dari Naungan ke Halaman pada Arsitektur Kafe - Redyantanu, Bramasta Putra (JAUR (JOURNAL OF ARCHITECTURE AND URBANISM RESEARCH), 2025)
This paper aims to reflect on the transformation of roofs from merely providing shelter to becoming active thematic spaces in cafe architecture. This study responds to the phenomenon of uniquely designed cafes, which leverage various spatial aspects, including roofs, to enhance the outdoor spatial experience. Roofs are no longer just protective coverings against the weather, but have the potential to be reimagined as imaginative, explorative active spaces. This study employs a descriptive qualitative approach based on case studies in Indonesia within a tropical context to illustrate the diverse roles and functions of roofs. The analysis is conducted by identifying the configuration of roofs as active spaces. The primary objective is to uncover how the application of roofs as active spaces involves various responsive design operations and strategies. The findings of this study highlight three key aspects of the new role of roofs: extended functionality, creative configurations, and functional construction. It is hoped that these insights will inspire cafe architectural designs to explore various other architectural aspects, beyond the traditionally understood limitations of roof functions.